2014
DOI: 10.2478/pjct-2014-0079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the ruthenium loading and barium addition on the activity of ruthenium/carbon catalysts in carbon monoxide methanation

Abstract: A group of supported ruthenium catalysts was prepared and tested in methanation of small CO amounts (7000 ppm) in hydrogen-rich streams. High surface area graphitized carbon (484 m 2 /g) was used as a support for ruthenium and RuCl 3 was used as a Ru precursor. Some of the Ru/C systems were additionally doped with barium (Ba(NO 3 ) 2 was barium precursor). The catalysts were characterized by the chemisorption technique using CO as an adsorbate. To determine the resistance of the catalysts to undesired carbon s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The increased intensity of CH 4 evolution was recorded at temperatures higher than 500 • C. It was revealed that the addition of lanthanum significantly lowers the amount of evolved methane [29]. The addition of barium further enhances this positive effect, in agreement with the earlier literature reports for Ba-Ru/C catalysts [40][41][42][43]. The achieved, positive result shows that both metals used in the catalytic system act as methanation inhibitors, despite of the chemical forms of lanthanum and barium in the doubly doped systems and that there is a possible interaction between their compounds.…”
Section: H 2 -Tprsupporting
confidence: 90%
See 2 more Smart Citations
“…The increased intensity of CH 4 evolution was recorded at temperatures higher than 500 • C. It was revealed that the addition of lanthanum significantly lowers the amount of evolved methane [29]. The addition of barium further enhances this positive effect, in agreement with the earlier literature reports for Ba-Ru/C catalysts [40][41][42][43]. The achieved, positive result shows that both metals used in the catalytic system act as methanation inhibitors, despite of the chemical forms of lanthanum and barium in the doubly doped systems and that there is a possible interaction between their compounds.…”
Section: H 2 -Tprsupporting
confidence: 90%
“…The H 2 -TPR measurements were performed in a thermogravimetric setup coupled with a mass spectrometer, according to the procedure presented in [40]. Netzsch STA 449C thermobalance equipped with a quadrupole mass spectrometer (Netzsch QMS 403C) was used for these measurements.…”
Section: Characterization Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many literature reports give information about the influence of different factors on the activity of oxide-supported Ru systems [1,6,7,12,13,16,17]. However, there are few papers dealing with the activity of ruthenium deposited on thermally modified carbons [18,19]. There is also lack of information concerning the effect of Ru crystallite sizes on the activity of Ru/C systems.…”
mentioning
confidence: 99%